2017
DOI: 10.7589/2015-12-350
|View full text |Cite
|
Sign up to set email alerts
|

OCCURRENCE AND RELEVANCE OFMYCOPLASMA STURNIIN FREE-RANGING CORVIDS IN GERMANY

Abstract: Several Mycoplasma spp. are well-known pathogens in poultry. In birds of prey, White Storks ( Ciconia ciconia ), and some waterfowl (Anatidae, Pelecanidae) species, mycoplasmas occur commonly and seem to be apathogenic or commensal and most likely belong to the physiologic microbial flora of the respiratory tract. In other bird species, such as Common Nightingales ( Luscinia megarhynchos ) and tits (Paridae), Mycoplasma spp. are absent in healthy birds. In corvids, the prevalence and role of Mycoplasma spp. in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…The results of the present study indicate that the investigated populations of passerine species (nightingales, great and blue tits) do not show any mycoplasmas as part of their physiological respiratory flora. However, prior studies indicated that some songbirds do show detectable mycoplasmas in their respiratory tract, as there were 7% of healthy free-ranging corvids tested positive for Mycoplasma sturni (Ziegler et al 2017). As all birds under study were tested negative for mycoplasmas and the prevalence of Mycoplasma spp.…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…The results of the present study indicate that the investigated populations of passerine species (nightingales, great and blue tits) do not show any mycoplasmas as part of their physiological respiratory flora. However, prior studies indicated that some songbirds do show detectable mycoplasmas in their respiratory tract, as there were 7% of healthy free-ranging corvids tested positive for Mycoplasma sturni (Ziegler et al 2017). As all birds under study were tested negative for mycoplasmas and the prevalence of Mycoplasma spp.…”
mentioning
confidence: 89%
“…In contrast, no mycoplasmas were found in healthy individuals belonging to other bird species e.g., psittacines or passerines (Lierz and Hafez 2009;Deem et al 2012). In corvids, mycoplasmas were isolated from diseased birds (Pennycott et al 2005), but also from 7% of clinically healthy individuals (Ziegler et al 2017). Therefore, corvids seem to occupy an intermediate position, so that mycoplasmas may play a role in respiratory disease.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…may represent facultative pathogens causing similar alterations when causing disease. Mycoplasma sturni is responsible for severe conjunctivitis in various bird species (Forsyth et al 1996;Frasca et al 1997;Ley et al 1998;Wellehan et al 2001), but was also found in healthy corvids (Ziegler et al 2017). Furthermore, corvids suffering from stressful conditions showed a higher prevalence (31%) than healthy individuals (7%).…”
mentioning
confidence: 99%
“…may occur, the detection of mycoplasmas does not necessarily lead to the diagnosis of a mycoplasmosis, and species differentiation is required. 15,20 Infections with avian mycoplasmas can be detected indirectly by a serologic assay or directly by methods including conventional isolation and identification as well as genusspecific or species-specific PCRs. 11 However, many laboratory tests are only available and validated for pathogenic avian mycoplasmas in poultry.…”
mentioning
confidence: 99%